PENGUATAN KEBANGSAAN MELALUI PRODUK RANCANG BANGUN MESIN PENCACAH PLASTIK SINGLE SHAFT SKALA RUMAH TANGGA - Kasyafullah, Muhammad Salik; Suryaman (JURNAL KEBANGSAAN RI, 2023)
The use of plastic as a packaging material and other equipment has caused environmental problems. The longer it accumulates, because plastic waste is not easily destroyed by rain and sun or microbes that live in the soil, this increasing environmental damage. In order to overcome this environmental problem, you can apply 3R (Reduce, Reuse, Recycle) by recycling plastic waste and reprocessing it into plastic ore or into plastic molding products. The purpose of this research is to produce a plastic shredder capable of chopping plastic waste according to the target to be achieved with a Shredder Machine design system with two edge cutters for cutting plastic waste, Solidworks is used to produce blade geometry and shape, blade material used is SS400 which has been carburized to make it stronger and more resilient, from the calculation process the plastic chopper obtained 0.45 Hp With a rotation of 47 RPM and a shaft diameter of 28 mm with a total of 14 Rotating Blades and 40 Silent Blades the production process obtained 62 kg/hour